Pengembangan Masyarakat Berbasis Budaya Lokal di Desa Efule Kecamatan Namrole, Kabupaten Buru Selatan - Fransina Matakena; Piter.J. Pelupessy (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses how the people of Efule village can maintain diversity in their local culture. Community development based on local culture is a development strategy that places local wisdom as the basis of values, knowledge, and various practices in the community empowerment process. The purpose of this study is to explain the local cultural values that can be integrated into community development efforts in order to achieve inclusive and sustainable development . The research method used in this study is descriptive qualitative research with a participatory approach through direct interviews and literature studies on various local community development practices. The results of the study indicate that local culture plays an important role in shaping social interaction patterns and support mechanisms for empowerment programs. In addition, the involvement of traditional and community leaders in the application of values such as mutual cooperation and social solidarity has been proven to strengthen a sense of ownership and collective responsibility for development. Integration into local culture in development policies needs to be maintained as a form of development.